Strategi Badan Pendapatan Daerah Dalam Mengimplementasikan Peraturan Walikota Nomor 114 Tahun 2020 di Kota Pekanbaru - Yuni Kastika; Adianto Adianto (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is motivated by the Pekanbaru City government's policy to reorganize the potential of local taxes, one of which is an effort to increase local revenue through the land and building tax sector. This study aims to analyze the Strategy of the Regional Revenue Agency in Implementing Mayor Regulation Number 114 of 2020 in Pekanbaru City. The method used in this research is descriptive qualitative, with data collection techniques using interviews, observation, and documentation. This study uses Robbins' theory in Yunus (2016) with four indicators, namely: innovation strategy, market differentiation strategy, outreach strategy, and cost control strategy. Based on the results of the study, it can be concluded that the strategy of the regional revenue agency in implementing mayoral regulations number 114 of 2020 in Pekanbaru City has not run optimally. The inhibiting factors in carrying out this strategy are incomplete data collection, and the lack of socialization costs. So that this has an influence on the Strategy of the Regional Revenue Agency in Implementing Mayor Regulation Number 114 of 2020 in the city of Pekanbaru..